Use of ultrasound in the diagnosis of cleft lip and palate during prenatal care: an integrative review (Research, Society and Development, 2022)
Introduction: Developmental malformations during the embryonic period are health concerns, their effects can range from aesthetic discomforts to incompatibility with life. In the context of dentistry, the main malformation reported is clefts and fissures that affect the lip and palate. In this context, planning given by a good diagnosis even during child prenatal care can help the family in planning measures to assist in the child's development. Objective: To address the importance of early diagnosis using ultrasound in the care of cleft patients for pediatric dentistry. Methodology: The study was conducted as an integrative literature review with content analysis in a qualitative way. The searched databases were Pubmed, Embase, Scopus, Web of Science, and Cochrane Library with the search strategy “("Cleft Lip" AND "Cleft Palate") AND ("Prenatal Diagnosis") AND ("Ultrasonography, Prenatal") ”. Studies from the last 10 years that were written in Portuguese, English, or Spanish were selected. Abstracts, notes, and letters to the editor were excluded. Results and Discussion: At the end of the analysis, 11 studies were selected that met the inclusion criteria. All articles demonstrated the usefulness of ultrasonography in the diagnosis of clefts and clefts of the lips and palates from the second trimester of pregnancy. Conclusion: Although the method does not have total accuracy, ultrasound helps in the diagnosis of malformations. The dentist must understand the imaging exam to carry out planning interventions with the multidisciplinary team to enable a humanized and comprehensive follow-up of the child.